Levels of cross-resistance to pyrethroids conferred by the Vssc knockdown resistance allele 410L+1016I+1534C in Aedes aegypti. - Juan J Silva; Cedric N Kouam; Jeffrey G Scott (Public Library of Science (PLoS), 2021)
Aedes aegypti is a primary vector of viral pathogens and is responsible for millions of human infections annually that represent critical public health and economic costs. Pyrethroids are one of the most commonly used classes of insecticides to control adult A. aegypti. The insecticidal activity of pyrethroids depends on their ability to bind and disrupt the voltage-sensitive sodium channel (VSSC). In mosquitoes, a common mechanism of resistance to pyrethroids is due to mutations in Vssc (hereafter referred as knockdown resistance, kdr). In this study, we found that a kdr (410L+V1016I+1534C) allele was the main mechanism of resistance in a pyrethroid-resistant strain of A. aegypti collected in Colombia. To characterize the level of resistance these mutations confer, we isolated a pyrethroid resistant strain (LMRKDR:RK, LKR) that was congenic to the susceptible Rockefeller (ROCK) strain. The full-length cDNA of Vssc was cloned from LKR and no additional resistance mutations were present. The levels of resistance to different pyrethroids varied from 3.9- to 56-fold. We compared the levels of resistance to pyrethroids, DCJW and DDT between LKR and what was previously reported in two other congenic strains that share the same pyrethroid-susceptible background (the ROCK strain), but carry different kdr alleles (F1534C or S989P + V1016G). The resistance conferred by kdr alleles can vary depending on the stereochemistry of the pyrethroid. The 410L+1016I+1534C kdr allele does not confer higher levels of resistance to six of ten pyrethroids, relative to the 1534C allele. The importance of these results to understand the evolution of insecticide resistance and mosquito control are discussed.